Variability of doublecortin-associated dendrite maturation in adult hippocampal neurogenesis is independent of the regulation of precursor cell proliferation - Plümpe, Tobias; Ehninger, Dan; Steiner, Barbara; Klempin, Friederike; Jessberger, Sebastian; Brandt, Moritz; Römer, Benedikt; Rodriguez, Gerardo Ramirez; Kronenberg, Golo; Kempermann, Gerd (BMC neuroscience, 2006)
In the course of adult hippocampal neurogenesis most regulation takes place during the phase of doublecortin (DCX) expression, either as pro-proliferative effect on precursor cells or as survival-promoting effect on postmitotic cells. We here obtained quantitative data about the proliferative population and the dynamics of postmitotic dendrite development during the period of DCX expression. The question was, whether any indication could be obtained that the initiation of dendrite development is timely bound to the exit from the cell cycle. Alternatively, the temporal course of morphological maturation might be subject to additional regulatory events. We found that (1) 20% of the DCX population were precursor cells in cell cycle, whereas more than 70% were postmitotic, (2) the time span until newborn cells had reached the most mature stage associated with DCX expression varied between 3 days and several weeks, (3) positive or negative regulation of precursor cell proliferation did not alter the pattern and dynamics of dendrite development. Dendrite maturation was largely independent of close contacts to astrocytes. These data imply that dendrite maturation of immature neurons is initiated at varying times after cell cycle exit, is variable in duration, and is controlled independently of the regulation of precursor cell proliferation. We conclude that in addition to the major regulatory events in cell proliferation and selective survival, additional micro-regulatory events influence the course of adult hippocampal neurogenesis.